Autonomy against the laws ruling the world as a condition of being really moral in the philosophy of Albert Schweitzer - Jarosz, Krzysztof (Studia Ecologiae et Bioethicae, 2004)
The ethics of Albert Schweitzer is subjectivist. He postulates the autonomy against the laws ruling the world and defines the general moral principle basing it on the inner experience of will-to-live. This comes from his conviction that we are not able to discover the meaning of the world's existence. He suggests an act of cognitive resignation - stopping to search for the meaning of the world and turning towards one's inside. Schweitzer finds the laws ruling the world to be cruel, allowing killing other creatures. A moral human being will never accept such rules. Striving to be faithful to the inner truth of his will-to-live, he will totally affirm the life opposing everything that happens around him. Schweitzer's postulate ignores the truth about the world. It is an attractive utopia of being good within a world that is full of destruction. Schweitzer, however, does not care that his postulates are impossible to be fulfilled.